Pergeseran Fungsi Hukum Pidana dalam Sistem Ketatanegaraan Indonesia: Dari Ultimum Remedium ke Political Control - Kholik, Muhamad Abdul; Zulfaidah, Rena (Sharia Journal and Education Center Publishing, 2025)
Criminal law in Indonesia has undergone a significant transformation in line with the enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) and Law Number 20 of 2025 concerning the Integrated Criminal Justice System (SPPT). This study analyzes the shift in the function of criminal law from the principle of ultimum remedium to the practice of political control in the context of Indonesian constitutionality. Through normative legal research methods with analytical approaches and regulatory comparisons, the research reveals that although the 2023 Criminal Code and the 2025 Criminal Code are designed to modernize the Indonesian criminal law system in accordance with the values of Pancasila and international standards, in practice there has been a significant paradigm shift. Criminal law no longer functions solely as an ultimum remedium when other legal instruments fail, but has shifted to become a tool of political control and an instrument to achieve certain goals at the constitutional level. This shift is reflected in the development of new categories of criminal acts, expanding investigators' discretion, changes in the evidentiary system, and the use of criminal law instruments for the regulation of areas that are not traditionally the domain of criminal law. The research identifies three main dimensions of this shift: (1) the materialization of criminal law through massive criminalization; (2) procedural instruments that facilitate political control; and (3) the constitutional context that encourages the politicization of criminal law. The conclusion of the study shows that a paradigmatic reorientation is needed in understanding the function of criminal law in Indonesia, accompanied by concrete efforts to restore the principle of ultimum remedium, strengthen the rule of law, and build an effective check-and-balance in the Indonesian constitutional system.